Cross-Species Functional Conservation and Possible Origin of the N-Terminal Specificity Domain of Mitochondrial Presequences - Lee, Dong Wook; Lee, Sumin; Min, Chan-Ki; Park, Cana; Kim, Jeong-Mok; Hwang, Cheol-Sang; Park, Sang Ki; Cho, Nam-Hyuk; Hwang, Inhwan (Frontiers in Plant Science, 2020)
Plants have two endosymbiotic organelles, chloroplast and mitochondrion. Although they have their own genomes, proteome assembly in these organelles depends on the import of proteins encoded by the nuclear genome. Previously, we elucidated the general design principles of chloroplast and mitochondrial targeting signals, transit peptide and presequence, respectively, which are highly diverse in primary structure. Both targeting signals are composed of N-terminal specificity domain and C-terminal translocation domain. Especially, the N-terminal specificity domain of mitochondrial presequences contain multiple arginine residues and hydrophobic sequence motif. In this study we investigated whether the design principles of plant mitochondrial presequences can be applied to those in other eukaryotic species. We provide evidence that both presequences and import mechanisms are remarkably conserved throughout the species. In addition, we present evidence that the N-terminal specificity domain of presequence might have evolved from the bacterial TAT (twin-arginine translocation) signal sequence